Teachers' Strategies in Teaching English During The Covid-19 Pandemic Period in SMP Muhammadiyah 2 Yogyakarta - Khofifah Idris (Universitas Ahmad Dahlan, 2022)
The learning process can be considered a success when the factors that affect it can actively contribute to ensuring that students fully understand the information and knowledge conveyed. The teacher unquestionably has a significant influence on the learning process and development of effective learning strategies. During the Covid-19 pandemic, this is a challenging duty for all teachers, and the teacher must be able to identify the most effective teaching strategy for children who are learning English. The object of this study is (1) To describe the strategies teachers use in teaching English in online learning classes during the Covid-19 pandemic at SMP Muhammadiyah 2 Yogyakarta and (2) To